Pengaruh Penyuluhan Gizi Seimbang Dengan Media Video, Poster Dan Permainan Kwartet Gizi Terhadap Pengetahuan Gizi Dan Status Gizi Siswa Di Sekolah Dasar Negeri Karangasem III Kota Surakarta - TUZZAHROH, Fatima, Elida Soviana, S.Gz., M.Gizi, Ruli Sudaryanto, SST.GZ (2015)
Introduction: Karangasem III elementary school is a school with the highest percentage (28.13%) in children malnutrition. One effort to improve the nutritional status is by increasing nutritional knowledge by nutrition counseling. Nutritional counseling is more effective when using media. Objective: Knowing the effects of nutritional counseling by the media videos, posters and quartet card game to the knowledge of nutrition and nutritional status of students in Karangasem III Elementary School Surakarta. Methods: This study is a pre-experimental design with one group pretestposttest programme. Sampling technique using stratified random sampling, total sample is 51 respondents. Media that used in this study are video, posters and quartet card game. Analysis of the data using Kolmogorof Smirnov test and Paired Samples T-Test test. Results: According to the results of Paired Samples T-test test to the nutritional knowledge values obtained p = 0.000 or p <0.05, that means there is an influence, whereas for the nutritional status values obtained p = 0.627 or p <0.05, that means there is no significant effect. Conclusion: There is the significant effect of nutrition counseling using videos, posters and quartet card game on nutritional knowledge of students but there is no significant effect on the nutritional status of students in karangasem III elementary school surakarta. Sugestion: videos, posters and quartet card game can be used as a medium of nutritional counseling and provide a good effect on nutrition knowledge for elementary school student.